Effect of Social Media on Local Coffee Shops - Chevy Herli Sumerli A.; I Nyoman Tri Sutaguna; Eka Kurnia Saputra; Dewi Kurniati; Ade Perdana Siregar (Budapest International Research and Critics University, 2022)
This article aims to discuss about effect of social media on Local Coffee Shops. This type of research is associative research. The population in this study is Local Coffee Shops at Medan City. The sampling technique in this research is using purposive sampling technique. Based on these considerations, the number of research samples is 100 Local Coffee Shops at Medan City. Data analysis in this study using simple regression analysis. The results show that social media has significant effect on Local Coffee Shops at Medan City.